Unpacking the Learning Paradigm: Transforming Teacher Skills thru the Integration of Canva Microlearning for Enjoyable Classroom Management - Reni Agustiningsih; Imron Arifin; Sri Wahyuni; Yudhit Dian Putra (Journal of Practice Learning and Educational Development, 2026)
This research aims to reveal the transformation of Early Childhood Education (ECE) teachers' skills thru the integration of Canva-based microlearning in enjoyable classroom management. The phenomenon under study stems from the still limited ability of early childhood education (ECE) teachers to pedagogically utilize digital technology to create structured learning that aligns with the characteristics of young children. This research uses a qualitative approach with a case study design. The research participants consist of early childhood education teachers who actively use Canva in their teaching activities. Data were collected thru semi-structured interviews, participatory observations, and learning documentation, then analyzed using the Miles and Huberman interactive analysis model. The research results show several main themes, namely changes in how teachers interpret enjoyable learning, improvements in teachers' ability to manage children's attention and focus thru microlearning, enhancements in lesson planning skills, and increased learning interactions in the classroom. These findings indicate that Canva-based microlearning functions not only as a visual medium but also as a pedagogical tool in managing early childhood education (PAUD) classrooms. This research has implications for strengthening the theory of enjoyable learning and provides practical recommendations for the development of technology-based competencies for PAUD teachers.